Carbon and non-carbon support materials for platinum-based catalysts in fuel cells - Samad S.; Loh K.S.; Wong W.Y.; Lee T.K.; Sunarso J.; Chong S.T.; Wan Daud W.R. (Elsevier Ltd, 2023)
Carbon black; Catalyst activity; Fuel cells; Gas fuel purification; Platinum; Platinum alloys; Temperature; Carbon based materials; Carbon support materials; Carbon-based; Catalyst support material; Electrocatalytic activity; Low temperature fuel cells; Platinum based catalyst; Structural characteristics; Catalyst supports